Unraveling the unphosphorylated STAT3–unphosphorylated NF-κB pathway in loss of function STAT3 Hyper IgE syndrome - Karim, Adil; Garg, Rashi; Saikia, Biman; Tiwari, Abha; Sahu, Smrity; Malhotra, Mehak; Minz, Ranjana W.; Rawat, Amit; Singh, Surjit; Suri, Deepti (Frontiers in Immunology, 2024)
Background: Patients with loss of function Signal transducer and activator of transcription 3 related Hyper-IgE Syndrome (LOF STAT3 HIES) present with recurrent staphylococcal skin and pulmonary infections along with the elevated serum IgE levels, eczematous rashes, skeletal & facial abnormalities. Defective STAT3 signaling results in reduced Th17 cells and an impaired IL-17/IL-22 response primarily due to a compromised canonical Janus kinase-signal transducer and activator of transcription (JAK-STAT) pathway that involves STAT3 phosphorylation, dimerization, nuclear translocation and gene transcription. The non-canonical pathway involving unphosphorylated STAT3 and its role in disease pathogenesis however is unexplored in HIES. Objective: To elucidate the role of unphosphorylated STAT3-unphosphorylated NF-κB (uSTAT3-uNKκB) activation pathway in LOF STAT3 HIES patients. Methodology: mRNA expression of downstream molecules of unphosphorylated STAT3-unphosphorylated NF-κB pathway was studied in five LOF STAT3 HIES patients & transfected STAT3 mutants post IL-6 stimulation. Immunoprecipitation assays were performed to assess the binding of STAT3 & NF-κB to RANTES promoter. Results: Reduced expression of downstream signaling molecules of uSTAT3-uNKκB -complex pathway viz. RANTES, STAT3, IL-6, IL-8, ICAM1, IL-8, ZFP36L2, CSF1, MRAS & SOCS3 in LOF STAT3 HIES patients as well as different STAT3 mutant plasmids was observed. Immunoprecipitation studies showed reduced interaction of STAT3 & NF-κB to RANTES in HIES patients. Conclusions: Reduced expression of downstream signaling molecules, specially RANTES, and STAT3, confirmed the impaired uSTAT3-uNKκB pathway in STAT3 LOF HIES. Decreased levels of RANTES & STAT3 could be a significant component in the disease pathogenesis of Hyper IgE Syndrome.